Malaysian tourists’ motivation towards outbound tourism / Mohd Hafiz Mohd Hanafiah, Zulhan Othman...[et al] - Mohd Hafiz, Mohd Hanafiah; Zulhan, Othman; Muhammad Izzat, Zulkifly; Hazmal, Ismail; Mohd Raziff, Jamaluddin (Faculty of Hotel and Tourism Management, Universiti Tekonologi MARA Selangor, Puncak Alam Campus, 2010)
The Malaysian outbound tourism market is recognized as one of emerging consumer demand based on the amount of expenditure reported. Despite this, research relating to the motivations for Malaysian outbound tourism, especially the push and pull factors are scarce. Therefore, it is necessary to understand why people travel and choose a specific international destination, and in line with this, this paper conceptually examines the influence of culture, demographic variables and tourists’ motivations in destination selection.